The Effects of Rotating the Self Out of the Body in the Full Virtual Body Ownership Illusion. (April 2014) - Blom, Kristopher J; Arroyo-Palacios, Jorge; Slater, Mel
It has been shown that it is possible to induce a strong illusion that a virtual body (VB) is one's own body. However, the relative influence of a first-person-perspective (1PP) view of the VB and spatial coincidence of the real body and VB remains unclear. We demonstrate a method that permits separation of these two factors. It provides a 1PP view of a VB, supporting visuomotor synchrony between real body and VB movements, but where the entire scene including the body is rotated 15° upwards through the axis connecting the eyes, so that the VB and real body are coincident only through this axis. In a within-subjects study that compared this 15° rotation with a 0° rotation condition, participants reported only slightly diminished levels of perceived ownership of the VB in the rotated condition and did not detect the rotation of the scene. These results indicate that strong spatial coincidence of the virtual and real bodies is not necessary for a full-body ownership illusion. The rotation method used, similar to the effects of vertical prisms, did not produce significant negative side-effects, thus providing a useful methodology for further investigations of body ownership.